2021
DOI: 10.3390/jcs5010019
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Strategies of Finite Element Simulation of Reinforced Concrete Beams Strengthened with FRP: A Review

Abstract: Fiber-reinforced polymer (FRP) composites do not only possess superior mechanical properties, but can also be easy to tailor, install, and maintain. As such, FRPs offer novel and attractive solutions to facilitate strengthening and/or retrofitting of aging, weakened, and upgraded structures. Despite the availability of general code provisions, the design and analysis of FRP-strengthened concrete structures is both tedious and complex—especially in scenarios associated with unique loading conditions. As such, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 56 publications
(67 reference statements)
2
29
0
Order By: Relevance
“…The spar uniaxial bar-like element is defined by two nodes with three degrees of freedom at each node which comprise of translations in the nodal x, y, and z directions. These reinforcing elements have the ability to simulate common nonlinear effects such as large deflection, plasticity, swelling, creep, and stress stiffening [11].…”
Section: Steel Reinforcementmentioning
confidence: 99%
See 1 more Smart Citation
“…The spar uniaxial bar-like element is defined by two nodes with three degrees of freedom at each node which comprise of translations in the nodal x, y, and z directions. These reinforcing elements have the ability to simulate common nonlinear effects such as large deflection, plasticity, swelling, creep, and stress stiffening [11].…”
Section: Steel Reinforcementmentioning
confidence: 99%
“…Naser et al [11] is one among the most recent study which indicates that the beams of concrete structures need to have adequate tensile strength and stiffness capacity to resist blast loading. The study further explains that connections of the structural elements need to offer a significant support to maintain the structural system integrity to absorb the explosion forces without collapsing.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years many solutions have been proposed for the upgrading and repair of existing structures, spanning from the most traditional techniques and materials to the most modern and innovative ones, making use of composite materials, which are increasingly adopted not only for masonry structures, but also for reinforced concrete structures [38,39], even including some unconventional coupling [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Plate-end debonding is a very common failure mode of the strengthened beams under loading, and therefore, it has become one of the most fundamental research topics in the past few decades. Numerous experimental (Deng and Lee, 2007; Lenwari et al, 2006; Rizkalla et al, 2008; Yu et al, 2011; Zeng et al, 2018) and theoretical studies (De Lorenzis and Zavarise, 2009; De Lorenzis et al, 2013; Haghani et al, 2009; Naser et al, 2021; Schnerch et al, 2007; Smith and Teng, 2001; Stratford and Cadei, 2006; Teng et al, 2002, 2015) have investigated the plate-end debonding failure in the FRP-strengthened beams at ambient temperature. The existing studies have demonstrated that high interfacial shear and peeling stresses at the plate end contribute to the plate-end debonding failure.…”
Section: Introductionmentioning
confidence: 99%